Clinical profile of patients undergoing coronary angiography with special reference to complications of coronary angiography - Raghav, Lumb; Waghmode, Parag; A., Parkar Matin; Pawar, Shubhadarshini (International Journal of Advances in Medicine, 2017)
Background: Cardiovascular Diseases (CVD’s) remain the biggest cause of death worldwide. Recent trends suggest that disease incidence has escalated and has started affecting younger age group also. Incidence of CVD’s has been on increasing trend not only in urban areas but in rural areas also. Aim of this research is to study clinical profile and complications in patients undergoing coronary angiography. Methods: 100 patients admitted in hospital who were planned for coronary angiography were selected. All routine investigations, Hba1c if patient is known diabetic, Serology, ECG, CXR were done at the time of admission. General physical and local examinations were performed at the end of procedure, after 12, 48 and 72 hours of coronary angiography. Results: Acute Myocardial Infarction (AMI) is the commonest indication for CAG in this study group. Out of 100 patients who underwent CAG, complications occurred in 29 individuals. Only 3 types of complications- Haematoma, Anaphylactoid reactions and Contrast Induced Nephropathy (CIN) are observed in this study. Conclusions: Hypertension, obesity, family history of IHD in first degree relatives and DM are important risk factors for IHD. Most common complication of CAG is haematoma. Females patients are more predisposed for all complications DM, HTN, advanced age and CHF are independent risk factors for developing CIN.